Perancangan Jaringan Untuk Supporting Integrasi Data Disabilitas Di Daerah Istimewa Yogyakarta Menggunakan Aplikasi Cisco Packet Tracer - Ahmad Syarif; Rr Yuliana Rachmawati; Joko Triyono (Jurnal Jarkom, 2016)
Progress and technological developments in the field of computers nowdays, is very rapidly, both hardware (hardware) and software (software). This can be seen in the era of information technology as it is now, for example, the utilization of internet media in the various agencies or schools in the data management that can’t be far apart from computer.Office of DIY province, Office districts, the Central Bureau of statistics, Ciqal Organization, Institutions and Donor agencies in the province of special region of Yogyakarta (DIY) as a whole already use internet network but it is not connected each other. Therefore, the design of the simulation of network is done using Sisco Packet Tracer application, so that all buildings can be connected each other and can exchange the information in a network where the server is located in the Centre of Yogyakarta office building. All the building techniques using point to point by adopting the topology star for connecting each other. Simulation design of the provincial office network design DIY, Office districts, the Central Bureau of statistics, Institutions and Donor agencies in the province of Special region of Yogyakarta (DIY) has been successfully carried out and have been connected properly and is ready to be applied to real life.